Digital Tax Transformation and Corporate Tax Accounting Quality: Evidence From Indonesia - Serly Novianti; Aljufri; Zaharman (Universitas Muhammadiyah Malang, 2026)
Research objectives: This research endeavors to investigate the impact of the implementation of the Core Tax System on the quality of tax accounting, with transparency serving as a mediating variable among corporate taxpayers in Indonesia.. Methods: This research employs a quantitative approach using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The data were collected through questionnaires distributed to 150 respondents who are directly involved in tax reporting activities in companies located in Pekanbaru, Riau. The sampling technique used purposive sampling, and data were analyzed using SmartPLS. Results: The empirical findings indicate that the Core Tax System exerts a positive and statistically significant influence on transparency, while transparency demonstrates a robust positive impact on the quality of tax accounting. Moreover, the Core Tax System is observed to have a direct impact on the quality of tax accounting. Additionally, evidence suggests that transparency serves as a partial mediator in the association between the Core Tax System and the quality of tax accounting. The proposed model accounts for 41% of the variance in transparency and 57% in the quality of tax accounting. Practical implications: The results indicate that enterprises ought to not merely implement digital taxation frameworks but also augment transparency protocols to elevate the standards of tax accounting. For legislators, reinforcing system interoperability and ensuring data availability is crucial in order to optimize the efficacy of digital taxation initiatives. Originality/novelty: This research enriches the academic discourse by presenting transparency as a mediating construct within the nexus connecting the Core Tax System and the quality of tax accounting. Furthermore, it amalgamates agency theory with the framework of accounting information systems to elucidate the underlying mechanisms associated with the implementation of digital taxation.